Organic fluorinated group / inorganic lithium fluoride gradient composite protective film and preparation method and application thereof in battery negative electrode protection

By depositing organic fluorinated groups/inorganic lithium fluoride gradient composite protective film on the surface of metal negative electrodes, separators or solid electrolytes of lithium-ion batteries, the problem of metal negative electrode dendrites is solved, the battery cycle life is extended and the overall performance is improved .

CN119411082APending Publication Date: 2025-02-11CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411314259.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The metal negative electrode in existing lithium-ion batteries is prone to form dendrites during circulation, resulting in short cycle life and high safety risks. Existing solutions such as adjusting the composition of the electrolyte or using solid electrolytes have defects.

Method used

The gradient composite protective film is used to deposit the metal negative electrode, separator or solid electrolyte surface through vacuum sputtering technology to form a gradient composite protective film, which physically suppresses and polarization fields to redistribute lithium ion flux. Inhibit the production and growth of dendrites.

Benefits of technology

It effectively extends the cycle life of the battery, improves the Coulomb efficiency and capacity retention rate, reduces the overpotential, and improves the overall performance and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411082A_ABST
    Figure CN119411082A_ABST
Patent Text Reader

Abstract

The invention discloses an organic fluorinated group / inorganic lithium fluoride gradient composite protective film and a preparation method and application thereof in battery negative electrode protection, and belongs to the technical field of batteries. The organic fluorinated group / inorganic lithium fluoride gradient composite protective film is a film composed of a fluorine-containing group and lithium fluoride. Wherein the distribution of the organic fluorinated group and the inorganic lithium fluoride component is gradient. The organic fluorinated groups are enriched on the side away from the substrate, and the lithium fluoride is enriched on the side close to the substrate. The organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared by the method has high Young's modulus and a large number of polar groups, can adjust the distribution of ions, enables a negative electrode to be uniformly deposited, inhibits the formation and growth of dendrites, effectively improves the coulombic efficiency, cycle performance and service life of a battery, and realizes long-term stable cycle of the battery. Moreover, the organic fluorinated group / inorganic lithium fluoride gradient composite protective film can be prepared on different parts of a battery according to actual working conditions, the process is simple, and the requirements on negative electrode protection under various conditions are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and specifically relates to an organic fluorinated group / inorganic lithium fluoride gradient composite protective film and a preparation method thereof, and application thereof in battery negative electrode protection. Background Art

[0002] With the development of new energy production and electric vehicles, there has been an urgent need for battery technology, among which lithium-ion batteries dominate. However, there are many problems with lithium-ion batteries currently used in practical applications, among which low energy density is the most prominent. Replacing traditional graphite negative electrodes with metal negative electrodes such as lithium-containing negative electrodes, sodium-containing negative electrodes, zinc-containing negative electrodes, and magnesium-containing negative electrodes can greatly improve battery energy density and solve the "range anxiety" problem of electric vehicles.

[0003] Metal anodes have extremely high theoretical specific capacity and low electrochemical potential, which helps to achieve high energy density. However, metal anodes are prone to form dendrites during cycling and penetrate the separator, resulting in short cycle life and high safety risks, making them difficult to use in practical applications.

[0004] To solve the problem of dendrite growth, current research focuses on adjusting the electrolyte composition to achieve uniform deposition or using solid electrolytes to prevent dendrite growth.

[0005] However, these methods all have obvious disadvantages, such as the expensive method of adjusting the electrolyte composition, the electrolyte additives will cause protection failure as the cycle is consumed, and the negative electrode will be consumed as the cycle continues and the negative electrode is irreversibly reacted. Solid electrolytes have low ionic conductivity, which increases the internal resistance of the battery and increases the weight of the battery. Therefore, finding an effective method to prevent dendrite growth and extend battery life is still an urgent problem to be solved. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an organic fluorinated group / inorganic lithium fluoride gradient composite protective film.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0010] The substrate is placed on a sample stage in a vacuum sputtering chamber, and the target is fixed on the cathode;

[0011] The target material includes one or more polymers and copolymers such as polytetrafluoroethylene, polyimide, polyperfluoroethylene propylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyperfluoroethylene propylene, polyvinylidene fluoride-hexafluoropropylene copolymer, etc.;

[0012] The vacuum sputtering chamber is evacuated, and sputtering is performed under the condition of argon gas with a flow rate of 5 to 50 sccm to obtain an organic fluorinated group / inorganic lithium fluoride gradient composite protective film deposited on the substrate.

[0013] As a preferred embodiment of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film described in the present invention, the substrate contains a metal negative electrode such as a lithium negative electrode, a sodium negative electrode, a zinc negative electrode and a magnesium negative electrode, a diaphragm or a solid electrolyte.

[0014] As a preferred embodiment of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film of the present invention, the lithium-containing negative electrode is a metal or alloy material containing lithium element.

[0015] As a preferred embodiment of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film of the present invention, the sodium-containing negative electrode is a metal or alloy material containing sodium element.

[0016] As a preferred embodiment of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film of the present invention, the zinc-containing negative electrode is a metal or alloy material containing zinc element.

[0017] As a preferred embodiment of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film of the present invention, the magnesium-containing negative electrode is a metal or alloy material containing magnesium element.

[0018] As a preferred scheme for the preparation method of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film described in the present invention, the diaphragm includes a polypropylene film, a polyethylene film, a double-layer PP / PE composite film, a three-layer PP / PE / PP composite film, a glass fiber diaphragm or a non-woven fabric diaphragm.

[0019] As a preferred scheme for the preparation method of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film described in the present invention, the solid electrolyte includes an oxide solid electrolyte, a halide solid electrolyte, a sulfide solid electrolyte or a polymer lithium salt composite solid electrolyte.

[0020] As a preferred embodiment of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film of the present invention, the thickness of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film is 0.005 to 10 μm.

[0021] As a preferred solution of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film described in the present invention, wherein: the sputtering power is 40 to 100W.

[0022] As a preferred solution of the method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film of the present invention, the vacuum degree in the sputtering chamber is 0.1-5Pa.

[0023] Another object of the present invention is to overcome the deficiencies in the prior art and provide an organic fluorinated group / inorganic lithium fluoride gradient composite protective film.

[0024] Another object of the present invention is to overcome the deficiencies in the prior art and provide an organic fluorinated group / inorganic lithium fluoride gradient composite protective film for use in battery negative electrode protection.

[0025] Beneficial effects of the present invention:

[0026] (1) The organic fluoride group / inorganic lithium fluoride gradient composite protective film prepared by the present invention can be modified on any surface of the metal negative electrode, diaphragm or solid electrolyte of the battery. In the method provided by the present invention, the fluorine-containing organic matter is decomposed by physical vapor deposition process and reacts with lithium metal in situ to form an organic fluoride group / inorganic lithium fluoride gradient composite protective film with high Young's modulus and strong polarity on the substrate surface. The distribution of organic fluoride groups and inorganic lithium fluoride components is gradient. The organic fluoride group is enriched on the side away from the substrate, and the lithium fluoride is enriched on the side close to the substrate. The protective film can redistribute the lithium ion flux through physical inhibition and polarization field, so that uniform lithium deposition is generated on the electrode surface, inhibiting the generation and growth of dendrites. Different from the characteristic that fluorine-containing electrolyte additives are gradually consumed with the cycle, the organic fluoride group / inorganic lithium fluoride gradient composite protective film can provide continuous and effective protection to the negative electrode during the long cycle of the battery.

[0027] (2) The organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared by the present invention is applied to batteries, which can effectively improve the coulombic efficiency and capacity retention rate of the battery, increase the cycle life and reduce the overpotential, improve the overall performance of the battery, and improve the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0029] Figure 1 This is a scanning electron microscope image of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 1 of the present invention.

[0030] Figure 2 The figure is a cycle-coulomb efficiency diagram of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film (diaphragm as substrate) of different thicknesses prepared by the present invention tested in a button battery.

[0031] Figure 3 This is a scanning electron microscope image of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared under a vacuum degree of 1 Pa in the sputtering chamber of the present invention.

[0032] Figure 4 This is a scanning electron microscope image of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared at a sputtering power of 80W in the present invention.

[0033] Figure 5 This is a cycle diagram of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film (the substrate is lithium metal) prepared by the present invention tested in a button battery. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0037] The diaphragm used in the present invention is a glass fiber diaphragm purchased from Whatman brand, GF / D type, with a thickness of 675 μm.

[0038] The lithium sheet used in the present invention is purchased from Zhongneng Lithium Industry, and has a thickness of 300 μm and a diameter of 14 mm.

[0039] The NCM622 positive electrode used in the present invention was purchased from CLUDE, with a surface density of 20 mg / cm 2 , gram capacity is 176mAh / g, and active substances account for 97%.

[0040] The copper foil positive electrode used in the present invention is purchased from Kruder and has a thickness of 8 μm.

[0041] The electrolyte used in the present invention is 1M LiPF 6 -EC / DMC (v:v=1:1), the added amount was 100 μL.

[0042] The sample stage used in the present invention is a 5cm×5cm stainless steel sample stage.

[0043] Unless otherwise specified, the raw materials used in the present invention are commonly available in the market.

[0044] Example 1

[0045] This embodiment provides a method for preparing an organic fluorinated group / inorganic lithium fluoride gradient composite protective film, specifically:

[0046] 1) Place the glass fiber diaphragm substrate on the sample stage and fix the four corners, and place polytetrafluoroethylene as the target material on the cathode and fix it;

[0047] 2) Adjust the vacuum sputtering chamber so that the background vacuum is less than 3×10 -4 Pa;

[0048] 3) Introduce high-purity argon gas at a flow rate of 20 sccm, make the vacuum degree in the sputtering chamber reach 0.5 Pa, turn on the magnetron sputtering power supply, adjust the sputtering power to 45 W, and adjust the parameters so that the reverse power is zero;

[0049] 4) Opening the sample baffle for sputtering, obtaining an organic fluorinated group / inorganic lithium fluoride gradient composite protective film with a thickness of 2 μm deposited on the substrate.

[0050] The surface morphology was characterized using a Hitachi S4800 scanning electron microscope. Figure 1 This is a scanning electron microscope image of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 1 of the present invention. It can be seen that the prepared protective film has a smooth surface and a uniform and flat structure.

[0051] Performance Test:

[0052] The lithium sheet, the glass fiber separator modified with the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 1, the electrolyte, the copper foil positive electrode, the stainless steel gasket, and the stainless steel spring are sequentially placed in the middle of the positive and negative electrode shells of the button battery to assemble a lithium-copper button battery;

[0053] The coulombic efficiency and cycle performance of the lithium-copper button battery were tested using a blue battery tester, with a discharge current of 1 mA / cm 2 , discharge capacity 2mAh / cm 2 , charging current 1mA / cm 2 , charging cut-off voltage 1V.

[0054] The coulombic efficiency and cycle life of the lithium-copper button cell assembled with the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 1 were tested, and the results are shown in Table 1.

[0055] Table 1

[0056]

[0057] It can be seen that when the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 1 is applied to lithium negative electrode protection, the cycle life reaches 116 cycles.

[0058] Example 2

[0059] The difference between this embodiment and embodiment 1 is that the thickness of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film in step 4) is adjusted to 1 and 3 μm respectively.

[0060] The remaining steps are consistent with those in Example 1, and a glass fiber diaphragm sample modified with an organic fluorinated group / inorganic lithium fluoride gradient composite protective film of this example is obtained.

[0061] The coulombic efficiency and cycle life of the button cell assembled with the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 2 were tested and compared with those in Example 1. The results are shown in Table 2.

[0062] Table 2

[0063]

[0064]

[0065] The cycle-coulomb efficiency diagram of lithium-copper button batteries prepared with different thicknesses of organic fluorinated group / inorganic lithium fluoride gradient composite protective films can be found in Figure 2 ,according to Figure 2As can be seen from Table 2, with the increase of membrane thickness, the initial coulombic efficiency also increases. This is because the increase in membrane thickness will slow down the side reaction between lithium metal and electrolyte; but the number of cycles when the capacity retention rate drops to 80% first increases and then decreases. This is because the thick membrane will increase the diffusion path length of ions, resulting in slower charge and discharge speeds and reduced ion diffusion efficiency, thereby affecting the capacity retention rate.

[0066] Comparative Example 1

[0067] Comparative Example 1 provides an unmodified glass fiber separator purchased from Whatman brand, GF / D type, with a thickness of 675 μm.

[0068] The coulombic efficiency and cycle life of the lithium-copper button battery prepared in Comparative Example 1 were tested and compared with those in Example 1. The results are shown in Table 5.

[0069] Table 5

[0070]

[0071] It can be seen that compared with Comparative Example 1, the coulombic efficiency of the battery assembled by the sample of Example 1 is increased by more than 26%, and the cycle life is increased by more than 56%, indicating that depositing the organic fluoride group / inorganic lithium fluoride gradient composite protective film in the present invention on the diaphragm for modification can have a significant protective effect on the lithium metal negative electrode.

[0072] In addition, the inventors found during the research that the vacuum degree and sputtering power during the sputtering process will affect the performance of the product. When the vacuum degree is higher than 0.5Pa, the film deposition rate is very slow. When the vacuum degree is lower than 0.5Pa, the excessively low vacuum degree may cause more microscopic defects in the film, thereby significantly reducing its coulomb efficiency and cycle life.

[0073] Figure 3 From the scanning electron microscope image of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared under the vacuum degree of 1 Pa in the sputtering chamber, it can be seen that its surface is not neat compared with Example 1, and irregularly arranged strip-like protrusions can be seen. This is because the vacuum degree is too low, which greatly increases the impurity gas molecules and affects the film quality.

[0074] At the beginning, as the sputtering power increases, the initial coulomb efficiency and cycle life increase accordingly. This is because lower sputtering power may cause the sputtering rate to slow down, and the formed film may be thinner or uneven. When the sputtering power exceeds 45W, the sputtering power is too high, so that the formed film has more defects, which significantly reduces the performance of the battery.

[0075] like Figure 4From the scanning electron microscope image of the organic fluoride group / inorganic lithium fluoride gradient composite protective film prepared under adjusted sputtering power of 80 W, it can be seen that its surface is rougher than that of Example 1, and irregular flaky protrusions are visible on the surface. This is because the sputtering power energy of 80 W is too high, resulting in uneven material deposition during the sputtering process, which leads to changes in the structural surface.

[0076] Example 2

[0077] This embodiment provides a method for preparing an organic fluorinated group / inorganic lithium fluoride gradient composite protective film, specifically:

[0078] 1) Place the lithium metal negative electrode substrate on the sample table and fix the four corners, and place polytetrafluoroethylene as a target material on the cathode and fix it;

[0079] 2) Adjust the vacuum sputtering chamber so that the background vacuum is less than 3×10-4Pa;

[0080] 3) Introduce high-purity argon gas at a flow rate of 20 sccm, make the vacuum degree in the sputtering chamber reach 0.5 Pa, turn on the magnetron sputtering power supply, adjust the sputtering power to 45 W, and adjust the parameters so that the reverse power is zero;

[0081] 4) Opening the sample baffle for sputtering, obtaining an organic fluorinated group / inorganic lithium fluoride gradient composite protective film with a thickness of 0.3 μm deposited on the substrate.

[0082] Performance Test:

[0083] The organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 2 was modified with a lithium sheet, a glass fiber separator, an electrolyte, an NCM622 positive electrode, a stainless steel gasket, and a stainless steel spring in the middle of the positive and negative electrode shells of the button battery to assemble a lithium-NCM622 button battery;

[0084] Use the Blue Battery Tester to test the cycle life, setting the charging current to 1.39mA / cm 2 , discharge current 1.39mA / cm 2 , charging cut-off voltage 4.3V, discharging cut-off voltage 3V.

[0085] The cycle life of the lithium-NCM622 button battery assembled with the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 2 was tested, and the results are shown in Table 6.

[0086] Table 6

[0087]

[0088] It can be seen that when the organic fluorinated group / inorganic lithium fluoride gradient composite protective film prepared in Example 2 is applied to lithium negative electrode protection, the cycle life reaches 143 cycles.

[0089] Comparative Example 2

[0090] Comparative Example 2 provides an unmodified lithium metal negative electrode purchased from Zhongneng Lithium Industry, with a thickness of 300 μm and a diameter of 14 mm.

[0091] The cycle life of the lithium-NCM622 button battery prepared in Comparative Example 2 was tested and compared with that of Example 2. The results are shown in Table 7.

[0092] Table 7

[0093]

[0094] The cycle diagram of lithium-NCM622 button battery made of lithium metal anode modified with organic fluorinated group / inorganic lithium fluoride gradient composite protective film and unmodified lithium metal anode is shown in Figure 5 .from Figure 5 As can be seen from Table 7, compared with Comparative Example 2, the cycle life of the battery assembled by the sample of Example 2 is improved by more than 34%, indicating that depositing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film of the present invention on lithium metal for modification can have a significant protective effect on the lithium metal negative electrode.

[0095] In summary, the present invention provides an organic fluoride group / inorganic lithium fluoride gradient composite protective film for a battery, a method for preparing an organic fluoride group / inorganic lithium fluoride gradient composite protective film, and a battery using a component modified by the above-mentioned organic fluoride group / inorganic lithium fluoride gradient composite protective film, wherein the organic fluoride group / inorganic lithium fluoride gradient composite protective film refers to a thin film composed of an organic group containing fluorine element and lithium fluoride. The distribution of the organic fluoride group and the inorganic lithium fluoride components is gradient. The organic fluoride group is enriched on the side away from the substrate, and the lithium fluoride is enriched on the side close to the substrate. The organic fluoride group / inorganic lithium fluoride gradient composite protective film has a high Young's modulus, and can redistribute the ion flux through the polarization field of the polar group, inhibit the generation and growth of dendrites, and effectively improve the cycle performance of the battery.

[0096] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an organic fluorinated group / inorganic lithium fluoride gradient composite protective film, characterized in that: include, The substrate is placed on a sample stage in a vacuum sputtering chamber, and the target is fixed on the cathode; The vacuum sputtering chamber is evacuated, and sputtering is performed under the condition of argon gas with a flow rate of 5 to 50 sccm, so as to obtain an organic fluorinated group / inorganic lithium fluoride gradient composite protective film deposited on the substrate; The target material includes one or more polymers and copolymers such as polytetrafluoroethylene, polyimide, polyperfluoroethylene propylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyperfluoroethylene propylene, polyvinylidene fluoride-hexafluoropropylene copolymer, etc.

2. The method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 1, characterized in that: The substrate includes a metal negative electrode such as a lithium-containing negative electrode, a sodium-containing negative electrode, a zinc-containing negative electrode, and a magnesium-containing negative electrode, a separator, or a solid electrolyte.

3. The method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 1 or 2, characterized in that: The lithium-containing negative electrode is a metal or alloy material containing lithium elements.

4. The method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 1 or 2, characterized in that: The sodium-containing negative electrode is a metal or alloy material containing sodium.

5. The method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 1 or 2, characterized in that: The zinc-containing negative electrode is a metal or alloy material containing zinc element.

6. The method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 1 or 2, characterized in that: The magnesium-containing negative electrode is a metal or alloy material containing magnesium.

7. The method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 1 or 2, characterized in that: The diaphragm includes a polypropylene film, a polyethylene film, a double-layer PP / PE composite film, a three-layer PP / PE / PP composite film, a glass fiber diaphragm or a non-woven fabric diaphragm; The solid electrolyte includes an oxide solid electrolyte, a halide solid electrolyte, a sulfide solid electrolyte or a polymer lithium salt composite solid electrolyte; the thickness of the organic fluoride group / inorganic lithium fluoride gradient composite protective film is 0.005 to 10 μm.

8. The method for preparing the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 1 or 2, characterized in that: The sputtering power is 40 to 100 W; The vacuum degree in the sputtering chamber is 0.1-5Pa.

9. The organic fluorinated group / inorganic lithium fluoride gradient composite protective film obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the organic fluorinated group / inorganic lithium fluoride gradient composite protective film according to claim 9 in battery negative electrode protection.